Development of a scale for elementary students' attitudes toward schooling - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
School dropout is a concern for Turkey. Factors associated with increased likelihood of school dropout include prior failure, nonacceptance by teachers and peers, poor school attendance and low level of involvement in school. This study has been part of a project investigating the problem of school drop out in the Kagithane district in Istanbul. A questionnaire assessing attitudes toward schooling has been developed to determine the school related factors of high school dropout. After the scale was improved based on data from the pilot study, 480 students from 13 schools took part in the study to assess scale's psychometric characteristics. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: School dropout; attitudes towards schooling; DROPOUT